Postoperative Opioid Dependence following Orthopaedic Foot and Ankle Surgery: A Cohort Study of 448 Patients. Issue 4 (22nd October 2020) - Bohl, Daniel D.; Hejna, Emily; Mehraban, Nasima; Lin, Johnny L.; Holmes, George B.; Lee, Simon; Hamid, Kamran S.
Category: Other Introduction/Purpose: Surgeon prescription of narcotic medications has been identified as a contributor to the nation's devastating opioid epidemic. The purpose of this study is to identify risk factors for postoperative opioid dependence following orthopaedic foot and ankle surgery. Methods: Four hundred and forty-eight patients undergoing orthopaedic foot and ankle surgery at a single institution over a 6- month period were identified. The Illinois Prescription Monitoring Program was used to track opioid prescriptions filled in the preoperative, perioperative, and postoperative periods. Preoperative use was defined as the filling of a prescription during the six months prior to the procedure, excluding the 30 days prior to the procedure. Postoperative dependence was defined as the filling of opioid prescriptions beyond the initial postoperative prescription. Baseline characteristics, including preoperative opioid use, were tested for association with opioid dependence. Results: The rate of preoperative opioid use was 20.5%. The rate of postoperative opioid dependence was 31.3%. Patients who used opioids during the preoperative period had the highest risk for postoperative opioid dependence, at 59.6% (RR=2.5, 95% confidence interval = 1.9-3.2, p<0.001; Table 1). Other baseline characteristics associated with postoperative opioid dependence included antiepileptic use (RR=1.8, p=0.001), recreational drug use (RR=1.7, p=0.022), Charlson comorbidity index >= 2 (RR=1.6, p=0.002), benzodiazepine use (RR=1.5, p=0.010), current smoker status (RR=1.5, p<0.001), age >=60 years (RR=1.4, p=0.022), body mass index >= 30 kg/m2 (RR=1.4, p=0.027), antidepressant use (RR=1.4, p=0.050), and <1 drink per week (RR=1.3 p=0.045). Conclusion: The single strongest predictor of postoperative opioid dependence was preoperative opioid use, which was associated with more than a doubling in risk. Of note, the chronicity of the foot or ankle condition did not predict postoperative opioid dependence. Preoperative discussion of opiate treatment duration, multimodal pain management strategies and judicious prescription of narcotics should be considered in patients with the above-noted risk factors in an effort to avoid dependence on this potentially addictive and harmful class of medications.